Estimation of Wind-Induced Pressures on a Low-Rise Building Using Quasi-Steady Theory - Wu, Chieh-Hsun; Kopp, Gregory A. (Frontiers in Built Environment, 2016)
A quasi-steady (QS) model that includes both the instantaneous wind azimuth and elevation angle is applied and extended to relate the instantaneous wind speeds and roof pressures for a typical low-rise building. The construction and validation of the QS vector model were done through the synchronized measurements of wind speed and building surface pressures on 1/50-scale model of the TTU-WERFL Building in a boundary layer wind tunnel. The results show that the QS predicted pressures are more highly correlated to the measurements when the elevation angle is included. A statistical method for estimating the probability density functions, based on the assumptions from the QS model, is derived and validated. This method relates the probability density function (pdf) of building surface pressures to the joint pdf of wind speed, azimuth angle and elevation angle.